Human interaction skills and employability at information technology internships - Costa-Lobo, Cristina (2017)
To implement internships with undergraduate students is a pedagogical option with some good results perceived by academic staff, employers, and among graduates. The Human Interaction Skills development as well as the attractiveness of such experiences for higher education students are topics assumed as core in the conception and management of the activities implemented in the undergraduate courses offered at the last three decades in computer science degree and in information systems technologies degree at one Portuguese private university. The objectives of this paper are to gather evidence of the Human Interaction Skills explained and valued at Information Technology Internships and to evaluate the importance and the relevance of these experiences in promoting employability after the Information Technology Internships. Data collection was based on the application of questionnaire to trainee supervisors and to students who have completed Information Technology Internships in the last decade at one Portuguese private university. The trainee supervisor, responsible for monitoring the student`s performance at Information Technology Internships, evaluates the following Human Interaction Skills: Motivation and interest in the activities developed, interpersonal relationship, cooperation in company activities, assiduity, ease of knowledge apprehension, compliance with norms, insertion in the work environment, productivity, initiative, ability to take responsibility, creativity in proposing solutions, and selfconfidence. The results show that in the concluding phase of these undergraduate courses students have positive levels of development of Human Interaction Skills and that these students, once they finish their degree, initiate remunerated work functions, mainly by invitation of the institutions in which they perform Information Technology Internships. Findings provided strong evidence of Human Interaction Skills advantages contribute to widen the analysis of its effectiveness in terms of future research and actions in regard to the transition from Higher Education pathways to the Labour Market.